Intervención psicopedagógica para la educación de la sexualidad responsable en adolescentes de básica superior de la Unidad Educativa “Quevedo”. - Espinoza Mendoza, Luz Mercedes (2025)
The research project entitled "Psychopedagogical Intervention for Responsible Sexuality Education in Adolescents of Upper Basic Education at Unidad Educative “Quevedo" seeks actions that support a psychopedagogical intervention program aimed at mitigating issues related to sexuality education in adolescents. It begins by outlining the current situation regarding the knowledge, attitudes, and practices related to sexuality within the educational institution under study. Once local and national statistical indices regarding teenage pregnancies, sexually transmitted diseases, inappropriate sexual relationships involving emotional manipulation, deterioration of virtues and human values, and consequences on family well-beingrelated to the studied population sample are differentiated, the project analyzes the deficiencies in sexuality education from the institutional educational perspective, family participation, and shared social responsibility. The goal is to develop preventive and educational action lines through psychopedagogical programs that, starting from Unidad Educativa "Quevedo," serve as a guiding framework for the continuation of similar educational processes. The quantitative-qualitative methodological process has allowed for an in-depth examination of the problem, highlighting the real needs of the current educational context. This initial process concludes by promoting initiatives to incorporate new training methods into the curriculum for the comprehensive development of adolescents. Interinstitutional collaboration efforts should foster further research with greater long- term significance and impact, contributing to the design, development, and planning of future preventive and educational action lines within psychopedagogical programs at Unidad Educativa "Quevedo."